Social Relations Of Religious Figures With The Village Community Of Segamit, Semande Darat Ulu, Muara Enim Regency - Wildan Nur Hidayat; Nur Indah Tiara; Della Yulanda; Jendri Nopran Satria (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study examines the social relationships between religious leaders (kyai and santri) and the local community in Segamit Village, Semende Darat Ulu Subdistrict, Muara Enim Regency, South Sumatra. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document review at the Raudhatul Mubtadi'in Islamic Boarding School. The findings reveal that the social bonds between religious figures and the surrounding community are built upon three interrelated foundations: shared religious activities, local cultural traditions, and mutual cooperation in daily life. Kyais play a dual role as spiritual authorities and informal social leaders whose guidance extends far beyond the walls of the Islamic boarding school. This study also identifies enabling factors particularly shared worship events, strong norms of mutual aid, and open channels of communication as well as inhibiting factors such as the encroachment of digital technology on direct social interaction and the Islamic boarding school's demanding internal schedule. These findings contribute to a broader understanding of how Islamic educational institutions function as pillars of community cohesion in rural Indonesia.